FV 9. Diffusion Tensor Imaging in Neuromuscular diseases - A novel method for quantification of muscle degeneration in myopathy patients. Issue 9 (September 2016) - Rehmann, R.; Schlaffke, L.; Vorgerd, M.; Tegenthoff, M.; Schmidt-Wilcke, T.
Abstract : Introduction: The field of rare Myopathy diseases lacks in non-invasive, however quantifiable methods for evaluating states of diseases as well as monitoring disease progress and therapies. Therefore Diffusion Tensor Imaging (DTI) for non-invasive indirect representation of muscle fibre structure of human skeletal muscles, is a very promising tool for investigating and quantifying disease dependent structural changes, which cannot be observed using conventional imaging methods. DTI provides indirect measures of diffusion quantity and microstructure properties of skeletal muscles by fractional anisotropy (FA) and mean diffusivity (MD). Although there is raising evidence of this method in healthy control groups, little is known about disease dependent changes in diffusion properties. Aims: In the current study we sought to investigate, whether differences between healthy control subjects and patients with Glycogen storage disease type V (also known as McArdle disease), a metabolic disorder, can be quantified by using DTI as a non-invasive method. Specifically we were interested in defining parameters (e.g. FA or MD) that provide evidence for this disease and could therefore maybe used as an indirect marker for early disease stages. Methods: Conventional T1 weighted images as well as muscle diffusion weighted images were acquired from upper limbs of 12 healthy control subjects as well as from 5 (??) McArdle patients. Using a 3T Philips Achieva 3T x-Series MR with a 16 CH Sense XL-Torso coil, a 450 × 284 × 372 mm[c] FOV was imaged in approximately 20 min. All data analysis, including tractography for muscle separation and quantification was conducted, using Matlab based toolbox ExploreDTI. Results: Given the 12 healthy subject, we were able to generate norm values for the applied study setup. These norm values, including FA as well as MD, were created for six separate thigh muscles (M. vastus lateralis, M. Vastus medialis, M. biceps femoris, M. rectus femoris, M. Semitendinosus and M. Semimembranosus). Some of the McArdle patients showed partially significant deviations from these norm-values, mostly in the distribution of given FA-values. Conclusion/outlook: In this study we present diffusion dependent norm-values for six thigh muscles measured in a healthy population. Furthermore we provide first evidence, that myopathy specific changes in Glycogen storage disease type V could be observed non-invasively using diffusion tensor imaging approaches. Further research should focus more specifically on different types of glycogen storage disease to provide predictive measures for type and progress of the disease.